Evaluation of Improved Sickle for Paddy Harvesting in Central India - Abhijit Khadatkar , RR Potdar , Harsha Wakudkar , BS Narwariya; UC Dubey (Indian Journal of Extension Education, 2018)
Improved and local sickle were evaluated ergonomically for harvesting paddy crop with 10 farm women (Subjects) aged 22-45 years from Kachhi-berkheda village, Bhopal (Madhya Pradesh). Improved sickle was tested on farm women to improve work efficiency and to reduce the drudgery of farm women. The performance in respect to heart rate, cardiac cost, overall discomfort, body part discomfort and output were evaluated and data of improved and local sickle were compared. The results revealed that mean HRwork and oxygen consumption rate was 112 beats/min and 0.5 l/min with improved sickle, whereas it was 109 beats/min and 0.6 l/min with local sickle during paddy harvesting, respectively. The corresponding work pulse (∆ HR) was 34 beats/min. It was observed that there was 5.3 per cent increase in output with improved sickle. The total cardiac cost of work and physiological cost of work in improved sickle was recorded as 1251 and 42, respectively. About 28 per cent reduction in drudgery was observed with improved sickle in comparison with local sickle.